Assessment of transplacental and lactational genotoxicity of tembotrione in Wistar rats at different developmental stages by alkaline comet assay. (November 2021) - Mužinić, Vedran; Katić, Anja; Kašuba, Vilena; Micek, Vedran; Milić, Mirta; Želježić, Davor
Graphical abstract: Highlights: Dams were treated with tembotrione during gestation and/or lactation. Primary damage to DNA was evaluated in leukocytes and liver cells of the offspring. After gestation and lactation no DNA damage was recorded in examined pups' tissues. Tembotrione did not induce transplacental or lactational DNA damage in offspring. When estorus cycle was established, elevated DNA damage was found in dams' liver. Abstract: This paper assessed the potential of trans-placental and -lactational genotoxicity and oxidative stress induction of tembotrione, a naturally derived allelopathic herbicide. Several treatment protocols were applied to measure primary DNA damage by alkaline comet assay in leucocytes and liver. To address the oxidative stress induction, TBARS, ROS, SOD, CA, GSH-Px activity were recorded. The dams were treated from the first gestation day and pups sacrificed after birth. The second treatment protocol comprised treating the dams during gestation and lactation and sacrificing the pups at weaning. The third group of pups comprised offspring of dams that were treated in gestation and lactation and sacrificed in puberty. To address translactational genotoxicity, dams were treated in lactation only. Dams treated in gestation and lactation were sacrificed after reentering the estrous cycle and analyzed for DNA damage and oxidative stress. Tembotrione doses encountered in everyday human exposure, as estimated by the EFSA, were applied in dam treatment in consecutive days (ADI: 0.0004 mg/kg b.w./day, AOEL: 0.0007 mg/kg b.w./day, 1/500 LD50 4.0 mg/kg b.w./day). Although we observed mitigated DNA integrity at the dose of 4.0 mg/kg/b.w./day in female pubertal rats, we can conclude that at the conditions employed in the study low doses of tembotrione do not pose a risk for DNA damage of the offspring of treated dams. Contrary to this, the highest dose significantly affected all the oxidative stress parameters in the liver and plasma of pubertal females, CAT and GSH-Px in the liver of males and ROS and CAT of dams.